2015
DOI: 10.54386/jam.v17i2.1009
|View full text |Cite
|
Sign up to set email alerts
|

Determination of nitrogen and water stress with hyper spectral reflectance on maize using classification tree (CT) analysis

Abstract: Field experiments were conducted at the Tamil Nadu Agricultural University, Coimbatore, Tamilnadu, India during rabi (winter) season of 2013-14 with maize crop (TNAU maize hybrid Co 6). To ensure the stressed environment, the crop was subjected to two irrigation levels (IW/CPE: 0.80 and 0.50) and five staggered nitrogen levels (0, 50, 75, 100 and 125 % of recommended dose of nitrogen (RDN).The experiment was laid out in factorial randomized blocks design RBD (Factorial) with three replications. Hyper spectral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 8 publications
(9 reference statements)
0
1
0
Order By: Relevance
“…Ye et al [ 47 ] found that when leaf N content increased, spectral reflectance decreased, and this relationship was more significantly observed in the green to near infrared regions. Due to these relationships, if robust statistical models can be developed, hyperspectral leaf reflectance can be used as a proxy for rapid assessment of photosynthetic capacity [ 48 50 ], as well as non-destructive and real-time monitoring of leaf N content [ 51 , 52 ]. On the other hand, creating empirical models for hyperspectral data requires sophisticated model development techniques, and model robustness depends on the quality of sample data measured in the field [ 53 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ye et al [ 47 ] found that when leaf N content increased, spectral reflectance decreased, and this relationship was more significantly observed in the green to near infrared regions. Due to these relationships, if robust statistical models can be developed, hyperspectral leaf reflectance can be used as a proxy for rapid assessment of photosynthetic capacity [ 48 50 ], as well as non-destructive and real-time monitoring of leaf N content [ 51 , 52 ]. On the other hand, creating empirical models for hyperspectral data requires sophisticated model development techniques, and model robustness depends on the quality of sample data measured in the field [ 53 ].…”
Section: Introductionmentioning
confidence: 99%